2022
DOI: 10.3390/ijms23105593
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Focal Adhesion Kinase Restores Simulated Microgravity-Induced Inhibition of Osteoblast Differentiation via Wnt/Β-Catenin Pathway

Abstract: Simulated microgravity (SMG) inhibits osteoblast differentiation (OBD) and induces bone loss via the inhibition of the Wnt/β-catenin pathway. However, the mechanism by which SMG alters the Wnt/β-catenin pathway is unknown. We previously demonstrated that SMG altered the focal adhesion kinase (FAK)-regulated mTORC1, AMPK and ERK1/2 pathways, leading to the inhibition of tumor cell proliferation/metastasis and promoting cell apoptosis. To examine whether FAK similarly mediates SMG-dependent changes to Wnt/β-cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Based on evidence that integrin responses are involved in bone loss associated with microgravity, studies using simulated microgravity indicated that several pathways regulated by integrins, through focal adhesion kinase (FAK), mTORC1, AMPK, and ERK1/2, are affected by low gravity in an osteoblast-like cell line [220]. Microgravity was then shown to downregulate FAK, Wnt/Beta catenin, and signaling downstream of Wnt/beta catenin.…”
Section: Evidence For Integrin-mediated Response To Low Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on evidence that integrin responses are involved in bone loss associated with microgravity, studies using simulated microgravity indicated that several pathways regulated by integrins, through focal adhesion kinase (FAK), mTORC1, AMPK, and ERK1/2, are affected by low gravity in an osteoblast-like cell line [220]. Microgravity was then shown to downregulate FAK, Wnt/Beta catenin, and signaling downstream of Wnt/beta catenin.…”
Section: Evidence For Integrin-mediated Response To Low Gravitymentioning
confidence: 99%
“…As a consequence, several markers of osteoblast differentiation and bone formation were decreased. In a hind limb unloading model, bone loss was observed, and this was prevented by using an activator of FAK [220]. Although this pathway may contribute to bone loss in low gravity, FAK is crucial for many cell types under many conditions, and unless an FAK-targeting treatment could be focused on osteoblasts, this does not appear to provide a route for preventing bone loss in low gravity.…”
Section: Evidence For Integrin-mediated Response To Low Gravitymentioning
confidence: 99%
“…This was first recorded in the mid-1970s by Skylab astronauts, who experienced a monthly bone mass reduction of 1–2% compared to pre-flight and ground-based controls [ 3 , 4 ]. Subsequent investigations have highlighted the activation of the RANKL/RANK/OPG, PPARγ, and PKA/CREB signaling pathways in microgravity, whereas the Wnt/β-catenin and BMP/Smad pathways are suppressed, leading to enhanced bone resorption and inhibited bone formation [ 5 , 6 , 7 , 8 , 9 ]. (c) Prolonged use of medications like anticonvulsants, glucocorticoids, sedatives, or chemotherapeutic agents [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific facilities, such as the monoaxial clinostats Rotating Wall Vessel (RWV) and Rotary Cell Culture System (RCCS), and the Random Positioning Machine (RPM) can be used to create µg in research laboratories [14][15][16][17]. The majority of research in this field has primarily focused on specific cell types, such as osteoblasts/osteoclasts [18][19][20], myofibers [21], endothelial cells [22][23][24], stem cells [25,26], fibroblasts [27][28][29][30][31] chondrocytes [32], lymphocytes [33] and other immune cells [34], with limited attention given to kidney cells [35,36].…”
Section: Introductionmentioning
confidence: 99%